Use of advanced heart failure therapies in Duchenne muscular dystrophy. (June 2019) - Wittlieb-Weber, Carol A.; Villa, Chet R.; Conway, Jennifer; Bock, Matthew J.; Gambetta, Katheryn E.; Johnson, Jonathan N.; Lal, Ashwin K.; Schumacher, Kurt R.; Law, Sabrina P.; Deshpande, Shriprasad R.; West, Shawn C.; Friedland-Little, Joshua M.; et al.
Abstract: Background: As survival and neuromuscular function in Duchenne Muscular Dystrophy (DMD) improve with glucocorticoid therapy and respiratory advances, the proportion of cardiac deaths is increasing. Little is known about the use and outcomes of advanced heart failure (HF) therapies in this population. Methods: A retrospective cohort study of 436 males with DMD was performed, from January 1, 2005-January 1, 2018, with the primary outcome being use of advanced HF therapies including: implantable cardioverter defibrillator (ICD), left ventricular assist device (LVAD), and heart transplantation (HTX). Results: Nine subjects had an ICD placed, 2 of whom (22.2%) had appropriate shocks for ventricular tachycardia; 1 and 968 days after implant, and all of whom were alive at last follow-up; median 18 (IQR: 12.5–25.5) months from implant. Four subjects had a LVAD implanted with post-LVAD survival of 75% at 1 year; 2 remaining on support and 1 undergoing HTX. One subject was bridged to HTX with ICD and LVAD and was alive at last follow-up, 53 months after HTX. Conclusion: Advanced HF therapies may be used effectively in select subjects with DMD. Further studies are needed to better understand risk stratification for ICD use and optimal candidacy for LVAD implantation and HTX, with hopes of improving cardiac outcomes. Highlights: The proportion of cardiac deaths is increasing for males with Duchenne Muscular Dystrophy. Little is known about the use and outcomes of advanced heart failure therapies in this population. A large cohort of males with Duchenne Muscular Dystrophy was studied with focus on use of advanced heart failure therapies. ICDs were used in 9 subjects, with a significant rate of appropriate shocks (22.2%), no inappropriate shocks, and only 1 lead fracture. Four subjects had an LVAD implanted with post-implant survival of 75% at 1 year with 2 remaining on support and 1 undergoing heart transplantation successfully.